TRANSFORMASI SOSIAL DESA ADAT MENJADI DESA WISATA EDELWEIS: PERPEKTIF TEORI STRUKTURISASI “ANTHONY GIDDENS” - Setiyo Yuli Handono (Syarif Hidayatullah State Islamic University Jakarta, 2019)
The phenomenon of social change that occurred in Wonokitri Village, Sub-District of Tosari, Pasuruan Regency was very pronounced from the early 2000s until 2019. Changes not only change physical conditions even socially and economically also change very rapidly. These changes occur through planning and the role of parties from internal and external. The formulation of the problem includes: 1) who are the agents and structures in social change? Wonokitri Village (formerly known as Desa Adat) becomes a Tourism Village; The analysis in this research uses Anthony Giddens' structuration theory which explains the concept of agent and structure, space and time, as well as the relationship of structure with agent's social practice. This type of research is qualitative research with a case study method. Data collection uses observation, which is observing the condition of the village environment and various social practices of agents and the Wonokitri community in relation to the research context, interviews with key and additional informants, and gathering various documentation.The results showed that there were three main agents (tayuban / teropan: pardi and budi, jeep tourism and homestay: sukir) from the Wonokitri community who had influence in the community. The role he does in social change is through socialization, coordination, synergy and cooperation. The existing structure comes from the Wonokitri community and their social practices which are motivated by their practical and discursive awareness as well as the role of community leaders (Village Head: Pak Iksan), traditional leaders (Customary Chair: Pak Kadik) through their structural policies. The relationship between the agent and the structure in change occurs through the scheme of domination structure (control of the agent over the structure), continuing significance (the invitation of the agent to the structure), and achieving the scheme of legitimacy (justification for the agent's efforts by the structure).